Ekstraksi Ubi Jalar Ungu (Ipomoea batatas L.) Menggunakan Variasi Pelarut Serta Pemanfaatannya Sebagai Indikator Asam-Basa - Afandy, Moh. Azhar; Nuryanti, Siti; Diah, Anang Wahid M. (Universitas Tadulako, 2017)
Purple sweet potato (ipomoea batatas L.) is one source of carbohydrate. Purple sweet potato contains vitamins and minerals that needed by humans such as vitamin A, vitamin C, calcium, and iron. The sweet potato with purple flesh is widely used as natural dyes which are called anthocyanins. The study aim was to determine a suitable solvent to extract the purple sweet potato. Variation of solvent used namely methanol, methanol acidified with HCl 1% and solvent fractionation (n-hexane, ethyl acetate, and methanol). The extraction phase was divided into two, for flesh and for the skin of the purple sweet potato. The extraction results were then compared with phenolphthalein indicator and a methyl orange on acid-base titration. The results showed that the methanol acidified with HCl 1% provided a more stable color changes in acid-base testing, and the testing of phosphate buffer pH 1-12. Purple sweet potato extracts can be used as an acid-base indicator because it gave similar results with comparative indicators, phenolphthalein, and methyl orange.